Experience with invasive Candidainfections. Issue 881 (1st March 1999) - Girishkumar, Hanasoge; Yousuf, Arshad M; Chivate, Jayant; Geisler, Edward
Abstract : Between January and July 1995, 227 patients at the Bronx-Lebanon Hospital Center had positive fungal cultures. Candida spp were the most common fungi isolated. Forty-three patients with invasive disease, as indicated by fungus-positive blood cultures, became the focus of our study. C albicans caused fungaemia in 21 patients (49%). Twenty-eight patients (65%) were less than 50 years of age; three were neonates. The most common presenting symptoms were fever, chills, and weakness (20 patients, 47%). Thirty patients died, giving a mortality rate of 70%. The patients who died stayed in the hospital an average of 49 days. The highest mortality occurred among patients who became bacteraemic before or at the same time they became candidaemic (24 of 26 patients) or who were receiving broad-spectrum antibiotics (20 of 26 patients). We also found high mortality rates from invasive fungal infection among patients with HIV infection, a central venous catheter, and liver, renal, or respiratory failure. We did not find any increase in the incidence of invasive fungal infection or mortality among leukopenic or diabetic patients.